Prevalence of Obesity, Overweight and Underweight in Guidance School Students - M Sharafaddini (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2008)
Introduction: Obesity is an emerging major public problem throughout the world. Obesity, over weight and under weight are the most frequent nutritional disorders in children and adolescents in developing countries. The objective of this study was to assess the prevalence of obesity, over weight and under weight in adolescent students in Yazd. Methods: In a cross sectional study, weight and height of 794 guidance school students was collected and BMI [wt (kg)/ht(m2)] determined. The National Health and Nutrition Examination Survey III growth chart which has been adopted by World Health Organization wasused and BMI>95 percentile as obesity, BMI>85 and <95 as over weight and BMI<50 as under weight were defined. Results: Prevalence of underweight13.9% (male 9.8% , female 18%), over weight 12.9% (male17.2 , female 8.8%) and obesity 6.5% (male 8.8%, female 4.3%) was significant .( P< 0.001) Conclusion: Prevalence of obesity , overweight and underweight in adolescents of Yazd is of concern and prevalence of underweight is significantly higher in girls as compared to boys .